2014
DOI: 10.1111/medu.12615
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in medical school admission: insights from personnel recruitment and selection

Abstract: health care it requires. To this end, and to best serve its people, it should provide enough medical school positions, and residency training positions in the right number, mix and distribution, as well as access to licensure. This should occur in an equitable manner that ensures diversity that is appropriate to best serving the society in question. Then we will be walking the talk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Sixth, changing circumstances, such as higher selection ratios or applicants’ adapting behaviour to meet the selection criteria, may decrease the predictive validity of selection methods. Finally, with respect to adverse impact the main recommendation for medical schools would be to carefully think about a combination and weighting of academic as well as non‐academic selection instruments that would fit both the needs of validity and of diversity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixth, changing circumstances, such as higher selection ratios or applicants’ adapting behaviour to meet the selection criteria, may decrease the predictive validity of selection methods. Finally, with respect to adverse impact the main recommendation for medical schools would be to carefully think about a combination and weighting of academic as well as non‐academic selection instruments that would fit both the needs of validity and of diversity …”
Section: Resultsmentioning
confidence: 99%
“…Finally, with respect to adverse impact the main recommendation for medical schools would be to carefully think about a combination and weighting of academic as well as non-academic selection instruments that would fit both the needs of validity and of diversity. 4,17,32,65 Issues regarding reliability, validity and fairness of selection procedures have led to recent calls from the UK, the US and the Netherlands to replace medical school selection with lotteries. [66][67][68] However, my opinion is that, as long as we prevent our selection procedures from resembling expensive lotteries 69 by ensuring their reliability and validity while also taking the diversity amongst applicants into account, it is preferable to consider perceptions of applicants who favour methods that put them 'in control' 70 as well.…”
Section: Resultsmentioning
confidence: 99%
“…Age, gender and pu-GPA, and socio-demographic variables could largely explain the ethnicity-related disparities in theoretical examinations, but not in language, writing and clinical skills examinations. In order to retain non-traditional students in the medical education pipeline (Lievens 2015), medical schools must design assessment strategies and, if necessary, additional targeted support programmes that create a level playing field for a diverse student population.…”
Section: Resultsmentioning
confidence: 99%
“…A first practical implication is that medical schools should take care in designing assessment strategies to avoid possible unintended effects of certain types of examinations for certain groups of students. In analogy to the “validity-diversity dilemma” (Kravitz 2008) in selecting for a diverse medical school population, as recently described by Lievens (2015), medical schools face the challenge of balancing assessment strategies that not only fulfil the goal of assessing the required standards of competency, but also retain a diverse student population. In order to ensure that non-traditional medical students are not disadvantaged, diversity should be considered both in test construction and implementation (Wass et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a meta-analysis of 39 different studies, found Cronbach's alpha coefficients ranging from α=.43 to .94 . However, internal consistency of SJTs used in medical and dental contexts (Koczwara et al 2012, Patterson et al 2012a, 2014 have been found to consistently approach or exceed α=.70; the accepted value indicating good internal consistency (Kline 2000).…”
Section: How Reliable Are Sjts?mentioning
confidence: 99%